Statistical Assessment of Hydrological Feasibility for Converting Open-Cast Mine into Reservoir - Krishnaveni M. , Arunya KG , Ragavi G. (Mathematical Statistician and Engineering Applications, 2023)
Paravanar and its environment often receives high-intensity short-duration rainfall which results in flood hazards. But due to the lack of conservation of floodwater and high elevation difference within the basin, it is affected by drought in the subsequent years. The main aim of this study is to check the possibilities to convert the completed open cast mine into a water storage structure which is situated inside the basin and to make sure that it serves as both flood and drought mitigation measure. To identify the amount of rainfall, which is converted to direct runoff, rainfall-runoff estimation was done. The average runoff coefficient is estimated as 0.46. It states that almost half of the rainfall is converted into the runoff. Next, the magnitude of rainfall for different return periods such as 2, 5, 10, 25, 50, 100 and 200 years was predicted. Since it is a small river basin with high intensity short duration rainfall, storage is a major concern. There are two major tanks in Paravanar River Basin named Walajah Tank and Perumal Eri. The capacity of the Walajah tank is 90.72Mcft and the Perumal eri is 574Mcft. The capacity of the mine which is proposed to be converted as a water storage structure is also calculated and it is estimated as 1125Mcft. It provides higher storage than the prevailing tanks due to the depth of the mine. Therefore, if it gets converted then it will be a floodwater harvesting structure as well as a drought mitigation measure